2021
DOI: 10.3389/fpsyg.2021.604843
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Sunk Costs Depends on Attention to the Delay

Abstract: In the WebSurf task, humans forage for videos paying costs in terms of wait times on a time-limited task. A variant of the task in which demands during the wait time were manipulated revealed the role of attention in susceptibility to sunk costs. Consistent with parallel tasks in rodents, previous studies have found that humans (undergraduates measured in lab) preferred shorter delays, but waited longer for more preferred videos, suggesting that they were treating the delays economically. In an Amazon Mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 50 publications
7
41
0
Order By: Relevance
“…(Ott et al 2021) already acknowledge in their preprint that their model cannot explain behavior in the variants of Restaurant Row and Web-Surf that have a separate offer phase, and agree with our conclusions that decisions made in the offer and wait phases arise from different decision processes. As we have argued elsewhere Kazinka, MacDonald, and Redish 2021;Sweis, Abram, et al 2018), we agree that behavior in the offer and wait phases arise from different decision processes, consistent with both multiple-decision theories (Redish 2013 and commitment hypotheses (Gollwitzer, Heckhausen, and Steller 1990;Achtziger and Gollwitzer 2007). Although Ott et al acknowledge that offer and wait phases may well be different, they do not provide any explanation as to why the two phases are different as to sunk costs.…”
Section: The Data Finds No Sensitivity To Sunk Costs In the Offer Phasesupporting
confidence: 86%
See 4 more Smart Citations
“…(Ott et al 2021) already acknowledge in their preprint that their model cannot explain behavior in the variants of Restaurant Row and Web-Surf that have a separate offer phase, and agree with our conclusions that decisions made in the offer and wait phases arise from different decision processes. As we have argued elsewhere Kazinka, MacDonald, and Redish 2021;Sweis, Abram, et al 2018), we agree that behavior in the offer and wait phases arise from different decision processes, consistent with both multiple-decision theories (Redish 2013 and commitment hypotheses (Gollwitzer, Heckhausen, and Steller 1990;Achtziger and Gollwitzer 2007). Although Ott et al acknowledge that offer and wait phases may well be different, they do not provide any explanation as to why the two phases are different as to sunk costs.…”
Section: The Data Finds No Sensitivity To Sunk Costs In the Offer Phasesupporting
confidence: 86%
“…When humans were distracted from the delay countdown, we found that the sunk costs disappeared (Kazinka, MacDonald, and Redish 2021). Similarly, in rich environments (when the offer distribution is such that rodents can easily earn a large amount of food within the environment), we do not see sunk costs .…”
Section: The Data Finds a Lack Of Sensitivity To Sunk Costs In Some Conditionsmentioning
confidence: 59%
See 3 more Smart Citations